Trends in intentional abuse and misuse ingestions in school-aged children and adolescents reported to US poison centers from 2000-2020. (2nd January 2023) - Hughes, Adrienne R.; Grusing, Sara; Lin, Amber; Hendrickson, Robert G.; Sheridan, David C.; Marshall, Rebecca; Zane Horowitz, B.
Abstract: Context: Childhood and adolescent misuse and abuse exposures remain a serious public health challenge in the United States. This study aimed to describe recent trends and patterns of intentional substance misuse and abuse exposures among school-aged children and adolescents in the United States. Methods: This study was a retrospective cohort study of intentional misuse and abuse exposures in children 6 through 18 years reported to the National Poison Data System (NPDS) from January 1, 2000, through December 31, 2020. Demographic trends, reported clinical effects, treatments, management sites, and health outcomes were assessed overall and within four age categories: 6–9, 10–12, 13–15, and 16–18. Results: Between 2000 and 2020, there were 338, 727 cases regarding intentional misuse and abuse exposures for children ages 6 through 18 years old. Overall, misuse/abuse ingestions fluctuated over time, with a peak in 2011. The majority of intentional misuse/abuse ingestions occurred in males (58.3%), and more than 80% of all reported exposure cases occurred in youth aged 13 to 18. 32.6% of ingestions resulted in worse than minor clinical outcomes. Older age groups had a greater number of severe medical outcomes compared to younger age groups. Major or life-threatening exposures (including those resulting in death) were more common in males. Overall, deaths were rare ( n  = 450), 0.1%). Male sex, older age, abuse ingestions, exposure site of a public area or other residence, and multiple ingested substances were other factors associated with increased mortality. Marijuana exposure rates had the highest average monthly increase overall, with the most dramatic rise occurring from 2017 to 2020. Edible marijuana preparations accounted for the highest increase in call rates compared with all other forms of marijuana. Discussion and Conclusion: With over 330, 000 poison center cases reported during the 20-year study period, intentional substance misuse and abuse exposures substantially impact the pediatric population. The substances most commonly misused/abused are more widely available substances such as over-the-counter medications, household products and pharmaceuticals commonly prescribed to youth. Differences in age and sex were evident, with males and adolescents more likely to abuse and misuse substances. Our study describes an upward trend in marijuana misuse/abuse exposures among youth, especially those involving edible products. These findings highlight an ongoing concern about the impact of rapidly evolving cannabis legalization on this vulnerable population.